PENGARUH HARGA DAN KUALITAS PELAYANAN TERHADAP KEUNGGULAN BERSAING PADA BABERSHOP KOKO (STIE Rajawali Purworejo, 2021)
The aim of this research is to determine the effect of price and service quality on competitive advantage at Babershop Koko in Nampurejo Purwodadi village. The analytical technique used to analyze the effect of price and service quality. Data collection and surveys were carried out using questionnaires. The sample used a purposive sampling technique, totaling 50 respondents. This research uses data analysis methods, multiple regression, coefficient of determination t test and f test. Based on the research carried out, the results of the regression equation Y = 0.671 + 0.041X1 + 0.298X2 are finally obtained. This means that if the value of the price and service quality variables is objectified research is equal to zero, then the level or magnitude of the competitive advantage variable at Babershop Koko is 0.671. The results of the analysis of the coefficient of determination (R Square) explain that 21.1% is influenced by price and service quality variables, while 78.8% is influenced by other factors that were not studied, for example promotional factors and other consumer loyalty and so on. The results of partial hypothesis testing (t test) show a positive and significant influence between price and service quality on competitive advantage. The results of simultaneous hypothesis testing (f test) show a positive and significant influence between the price and service quality variables on competitive advantage.